Triagem neonatal para deficiencia de biotinidase no estado de Minas Gerais - Marilis Tissot Lara (2010)
Introduction: biotinidase deficiency is an inherited metabolic disorder, autosomal, recessive, caused by gene mutations in the biotinidase (BTD), located in chromosome 3p25. Usually this disorder is manifested through neurological and cutaneous abnormalities. The diagnosis consists in detection of the biotinidase enzyme activity in the plasma, when the patients are classified into two subgroups: profound or partial deficiency, when the enzymatic activity is, respectively, below 10% or between 10 and 30% of the mean normal activity. Studies on the prevalence of biotinidase deficiency in some countries show rates that vary from 1:40.000 to 1:60.000. In Brazil, there are few researches about its prevalence and disagreement on the found results. This paper mainobjective was to determine the prevalence of the biotinidase deficiency in the state of Minas Gerais, based on the screening test performed with dry blood samples collected from newborn heels evaluated by the Newborn Screening State Program / Programa Estadual de Triagem Neonatal. Material and methods: cross-sectional study carried out in the period from September 2007 to June 2008. Part of the newborn blood samples was collected on filter paper and sent to the NUPAD/FM-UFMG, for the newborn screening tests. The screening was done by the visual colorimetric qualitative method UMTEST BIOTINIDASA, developed in Cuba, and confirmed by quantitative dosage of biotinidase. The patients with confirmed biotinidase deficiency underwent clinical and neurologicalevaluation before and after beginning the treatment with biotina 10 mg, oral via, daily. Results: 182.942 newborns dry blood samples in duplicate were screened, from which 1.039 showed alterations. A second screening test was performed and 129 suspected samples were found for biotinidase deficiency. Among these, 120 newborns returned andsamples were collected for the quantitative study that confirmed the partial biotinidase diagnosis in 10 cases with equal distribution between sexes. There was no identification of profound biotinidase deficiency cases. All patients had normal clinical and neurological evaluation before and after the treatment beginning. The prevalence of biotinidase deficiency in the studied population was 1:18.289 live births. The visual colorimetric test was considered effective to identify the biotinidase deficiency cases and showed 100% relative sensitivity, 99,94% specific, 0,06% false positive and 8,3% positive predictive value. Conclusion: this study revealed prevalence of biotinidase deficiency of 1:18.289 live births in the State of Minas Gerais, from September 2007 to June 2008. Thisprevalence proved to be higher that the findings in other countries. It is noteworthy that all the identified cases were classified as partial biotinidase deficiency.